Employment, Disability, and Social Justice in the United States, Australia, and the United Kingdom - Parker Harris, Sarah; Owen, Randall (Développement Humain, Handicap et Changement Social / Human Development, Disability, and Social Change, 2018)
Liberal welfare states promote a human rights approach to disability policy that in practice has been constrained by neoliberal reforms. This research examines employment policy for people with disabilities in the United States, Australia, and the United Kingdom through a framework of Nancy Fraser’s theory of social justice. It employs a qualitative cross-national comparative methodology including focus groups and interviews with stakeholders of active welfare to work programs. The results suggest that neoliberal/individualized approaches are dominant within contemporary welfare to work programs and social justice/human rights need to be more effectively built into employment policy.